The Andean Community and its Effectson Industrial Internationalization Processes:A Case Study of Plastic, Food and Beverages Enterprises in Guayaquil - Jara, Carol (2014)
At present developing countries have found it necessary to set up integration mechanisms to remove barriers in order to promote trade. For this reason, countries have made efforts to encourage and develop local industries in order to offer attractive products to foreign markets and boost economic growth. In Latin America, the Andean Community (CAN) is one of the oldest integration process in Latin America. Ecuador, like other members of CAN, has had good results as a member of the CAN. Based on survey data this paper overviews some of the experiences, processes implemented, and commercialization efforts undertaken by manufacturing export companies in the manufacturing industrial sector (plastic, food and beverages) in the city of Guayaquil.